On English loanwords in Pitjantjatjara (2024)
The language borrowing process is characterized by the adoption and adaptation of lexical items from one language into another, a widespread practice resulting from various forms of linguistic contact such as trade, migration, colonization, and cultural exchange. This process, termed loanword adaptation, involves incorporating foreign words into the lexicon of the borrowing language, often guided towards factors of prestige or necessity (Campbell:2004). The adaptation of loanwords involves phonetic, phonological, morphological, and semantic changes, facilitated by the substitution of foreign sounds with phonetically equivalent ones in the recipient language. This investigation contributes to the linguistic knowledge and reinforces the intention to strengthen the understanding of the Pitjantjatjara Aboriginal language and to studies on the revitalization and expansion of Australian Aboriginal languages; therefore, it stablishes basis for further investigations on Autochthonous indigenous languages. In this study, we analyze mainly phonological and also some of the morphological adaptations of English loanwords in Pitjantjatjara, an Australian Aboriginal language. Despite differences in phonetic inventories between English and Pitjantjatjara, the recipient language demonstrates noteworthy adaptability in loanwords pronunciation. Through this qualitative analysis, we aim to deepen our understanding of the mechanisms involved in the adaptation of loanwords and shed light on the linguistic dynamics between English and Pitjantjatjara. By exploring how loanwords are assimilated into the phonological and morphological structures of the recipient language, this study contributes to the broader discourse on language contact and evolution.